Nationalism and Maulid Tradition: Internalizing Nationalism Values to Madurese Muslim Community - Siswanto Siswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
The diversity of cultures, races, ethnic groups, and religions has great potential to cause conflict. This condition indicates that the nationalism values of in the community decreased. This research examines the internalization of nationalism values through the maulid tradition for jamaah Majlis Maulid wa al-Ta’lim Riyadlul Jannah Madura. By using a qualitative approach with a phenomenological type, this study found that nationalism has an important meaning for the jamaah in building a peaceful life, strengthening brotherhood among the community and maintaining the integrity of NKRI. Internalization of the value of nationalism in the maulid tradition is done by reading the shalawat simth aldurar and chanting nasyid contained these values. The spirit of nationalism is seen in maintaining akhlak in following the shalawat readings, mutual respect, and a sense of belonging to the majlis and the caring attitude of the jamaah in helping others in the social activities